Inventarisasi Kearifan Lokal Etnis Karo dalam Pemanfaatan Etnobotani di Kabupaten Karo - Sihar Pandapotan; Khairat Khairat; Syahril Syahril (Mahesa Research Center, 2018)
This study aims to inventory various forms of Karo ethnic local wisdom in the use of various types of local plants, medical processing, food, cosmetics, rituals, and boards. Another goal is to analyze the potential of micro and macroeconomic elements in the marketing of processed plants. The cornerstone of thinking in this study is the concept of ethnobotany, ethnoecology, and local wisdom. This study uses qualitative research methods with a descriptive approach. Data collection techniques include participatory observation, in-depth interviews, document studies, and documentation. The results of the study revealed that there were at least 218 local Karo ethnic plants that grew and were known to be Karo ethnicity and their usefulness. Local plants for medical are 183 species, for culinary ingredients a total of 53 types, for cosmetics a total of 32 types, for magical number of 27 types, and for the cancellation of households (boards) of 7 types. Local plants / plants that function ethnobotany are those that have multiple functions, so that the total number of plants can exceed the number of local plants / plants used by the people. As for some of the Karo Ethnic local knowledge related to its processing, it was produced in the form of making karo oil, yellow/param, injecting betel nut, enough, spraying beltek, my erpangir rituals and others